Efeitos de diferentes tipos estressores sobre a memória e aprendizagem de ratas - Nascimento, Ezequiel Batista do (2013)
The exposure to stressors produces physiological changes of the organism in order to adapt the individual to the environment. Depending on the type, intensity and duration, stress can affect some cognitive functions, particularly processes of learning and memory. Several studies have also proposed that some level of anxiety would be necessary for memory formation. In this context, memories of previously aversive experiences may determine the manner and intensity with which are expressed fear responses, which explains the great interest in analyzing both anxiety and memory in animals. In addition, males and females demonstrate different reactions in relation to stressful stimuli, showing different levels of anxiety and differences in processing of the acquisition, retention and recall of information. Based on this information, the present study aimed to verify the effect of stress on learning, memory and anxiety behavioral parameters in rats exposed at different types of stressors of long duration (seven consecutive days): restraint (4h/day), overcrowding (18h/day) and social isolation (18h/day) in the different phases of the estrous cycle. Our results showed that the stress induced by restraint and social isolation did not cause changes in the acquisition process, but impaired the recall of memory in rats. Furthermore, it is suggested a protective effect of sex hormones on retrieval of aversive memory, since female rats in proestrus or estrus phase, characterized by high estrogen concentrations, showed no aversive memory deficits. Furthermore, despite the increased plasma levels of corticosterone observed in female rats subjected to restraint stress and social isolation, anxiety levels were unaltered, compared to those various stress conditions. Animal models based on psychological and social stress have been extensively discussed in the literature. Correlate behavioral responses, physiological and psychological have contributed in increasing the understanding of stress-induced psychophysiological disorders